Ribonucleic acid reduction of microbial biomass protein grown on coconut (Cocos Nucifera Linn.) sapal - Yusoo, Christine Sevilla
The study aimed to reduce the ribonucleic acid content of microbial biomass protein grown on coconut sapal. The initial ribonucleic acid (RNA) content of the MBP was 4.5528. The safe level for dietary nucleic acid is 2 g per day. Exceeding this limit could cause gout or gouty arthritis. Thus, the RNA content of the MBP must be reduced. Four methods of RNA reduction were evaluated. Of the four methods, only two were able to reduce RNA by 80%. These two methods (heat shock method and low-alkali-low-temperature) were then applied to the MBP. Using the low-alkali-high-temperature method of reduction, the RNA content was reduced to 2.0118. With the reduced-RNA-MBP, an adult can consume as much as 100 g of MBP without exceeding the limit for dietary nucleic acid. And, with the same amount of MBP, he can get 18.49 g protein.